CONCEPTUALIZING „POSTSOVIET STATE” - Мірошниченко, Г.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The state type, which appeared in postsoviet area, are analyzed in the article. The genesis and establishment of phenomenon, its specificity, features of the functioning and prospects are studied. The article focuses on the political elite of postsoviet area, their impact on the public and political life and the development of society, the nature of the privatization of perestroika and its long term effects.